2006
DOI: 10.1111/j.1439-0418.2005.01021.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eggplant transformed withoryzacystatingene onMyzus persicaeandMacrosiphum euphorbiae

Abstract: The effect of a genetically modified eggplant line expressing oryzacystatin on Myzus persicae (Sulzer) and Macrosiphum euphorbiae (Thomas) was examined. The transgenic eggplant reduced the net reproductive rate (R 0 ), the instantaneous rate of population increase (r), and the finite rate of population increase (k) of both aphids species compared with a control eggplant line. The mean generation time (T) of the aphids was unaffected by the transgenic plants. Age-specific mortality rates of M. persicae and M. e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 39 publications
0
24
1
2
Order By: Relevance
“…Moreover, many other studies have shown that PhyCys also affect the growth or survival of other inseets, nematodes and slugs on artificial diets or delivered through transgenic plants (Walker et al 1999;Lilley et al 2004;Ribeiro et al 2006;Konrad et al 2009;Carrillo et al 2010). In contrast, the anti-mite properties of cystatins have only been proven using the chestnut cystatin against house dust mite species (Pernas et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many other studies have shown that PhyCys also affect the growth or survival of other inseets, nematodes and slugs on artificial diets or delivered through transgenic plants (Walker et al 1999;Lilley et al 2004;Ribeiro et al 2006;Konrad et al 2009;Carrillo et al 2010). In contrast, the anti-mite properties of cystatins have only been proven using the chestnut cystatin against house dust mite species (Pernas et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Benchekroun et al, 1995;Leplé et al 1995;Girard et al, 1998aGirard et al, , 1998bCloutier et al, 1999Cloutier et al, , 2000Lecardonnel et al, 1999;Outchkourov et al, 2004;Ribeiro et al, 2006;Alvarez-Alfageme et al, 2007), but nonconclusive results were obtained in several cases, correlated with the onset of effective adaptive processes allowing target pests to overcome the deleterious effects of digestive protease inhibition. In practice, the inhibitory potency of protease inhibitors is critical for an effective inhibition of target pest digestive proteases in vivo (Urwin et al, 1995), as it directly determines the amount of recombinant protein needed in the modified host plant to provide sufficient antidigestive or pesticidal effects (Jongsma and Bolter, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The defense function has been inferred from the ability of PhyCys to inhibit the activity of digestive proteases from arthropods in vitro, in artificial diets as well as through bioassays on transgenic plants overexpressing PhyCys genes (Pernas et al, 1998;Atkinson et al, 2004;Ribeiro et al, 2006;Alvarez-Alfageme et al, 2007). Anti-mite activities and deleterious effects against phytopathogenic fungi and viruses have also been described for these inhibitors (Gutierrez-Campos et al, 1999;Pernas et al, 2000;Martinez et al, 2003;Abraham et al, 2006;Wang et al, 2008).…”
Section: ([Lvi]-[agt]-[rke]-[fy]-[as]-[vi]-x-[edqv]-mentioning
confidence: 99%